2020
DOI: 10.1111/sdi.12921
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to kidney transplantation in ESKD

Abstract: Kidney transplantation is the ideal treatment option for patients with end-stage kidney disease (ESKD). Since there is clear mortality benefit to receiving a transplant regardless of comorbidities and age, the gold standard of care should focus on attaining kidney transplantation and minimizing, or better yet eliminating, time on dialysis. Unfortunately, only a small percentage of patients with ESKD receive a kidney transplant. Several barriers to kidney transplantation have been identified. Barriers can large… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 97 publications
(277 reference statements)
0
8
0
Order By: Relevance
“…These findings are consistent with current waitlisting practices and previous studies that found that transplant providers were less likely to recommend patients for transplantation if they had comorbidities, had no social support, were non-adherent, and were older [29,30]. By contrast, experts did not identify race, ethnicity, socioeconomic status, or sex as important considerations in KT evaluation, despite waitlisting trends demonstrating lower access to KT among patients who are racial and ethnic minorities, women, or belong to a lower socioeconomic status [31][32][33][34][35][36]. It is important to note that even though providers did not explicitly list socioeconomic status as an important factor, social support and socioeconomic status are often related and thus decisions made during transplant evaluations could be unfavorable to patients of low socioeconomic status [30,37].…”
Section: Discussionmentioning
confidence: 84%
“…These findings are consistent with current waitlisting practices and previous studies that found that transplant providers were less likely to recommend patients for transplantation if they had comorbidities, had no social support, were non-adherent, and were older [29,30]. By contrast, experts did not identify race, ethnicity, socioeconomic status, or sex as important considerations in KT evaluation, despite waitlisting trends demonstrating lower access to KT among patients who are racial and ethnic minorities, women, or belong to a lower socioeconomic status [31][32][33][34][35][36]. It is important to note that even though providers did not explicitly list socioeconomic status as an important factor, social support and socioeconomic status are often related and thus decisions made during transplant evaluations could be unfavorable to patients of low socioeconomic status [30,37].…”
Section: Discussionmentioning
confidence: 84%
“…Hispanics are the largest and fastest growing ethnic minority group in the United States [10]. Numerous studies have identified disparities and barriers to kidney transplantation [11]. Unfortunately, disparities exist in all components of the transplantation process.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, disparities exist in all components of the transplantation process. Patient-, physician/provider-and system-related barriers have all been identified [11]. Studies have found that medical eligibility (such as age and comorbidities) does not explain ethnic disparities in transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…It is well-known that most patients who undergo kidney transplantation experience improvement in quality of life and improved survival when compared to patients who are waiting for kidney transplantation [ 2 ]. One of the major obstacles to kidney transplantation is the availability of a kidney donor, whether living or deceased [ 3 ]. The scarcity of such donations has led to an increasing number of patients waiting for a kidney transplant.…”
Section: Introductionmentioning
confidence: 99%